Geek Cuisine: Extending the Narrative of a Junk Food Gamer - Joelsson Tapani; Syrjälä Henna; Luomala Harri; Mäkilä Tuomas (Sage Publications, Inc., 2025)
In this article, we argue that the pervading hegemonic narrative on gamers’ eating culture emphasizing
hedonistic and fast foods is a one-sided storyline that highlights a potentially harmful gamer stereotype. To that end, we reveal the variety of gamers’ food consumption and broaden the narrative depicting the relationship between gamers and eating. Our literature review shows the dominance of the Junk Food Gamer narrative in extant research. However, by using a social constructionist narrative approach to analyze ethnographic observations and interviews, we show the emergence of an alternative, yet interrelated narrative: the Home Food Gamer. In addition, we utilize the idea of the Rubik's Cube to illustrate the actualization of multifaceted and contextually-bound gamer narratives that enable expanding the prevailing understanding of geek cuisine by shedding light on the variety of gamers’ food consumption. In this way, we participate in the ongoing discussion to unravel stereotypical assumptions about gamer culture.